Pemilihan Metode Akuntansi R&D dan Penghematan Pajak: Studi Empiris di Indonesia pada Era Covid-19 Era Vuca - Marcellina Vera Puspitasari; Dielanova Wynni Yuanita; Christine Novita Dewi (Politeknik Ganesha Medan, 2022)
This study examines the accounting method of expenditures for research and development by companies listed on the Indonesia Stock Exchange (IDX). This study uses the periode before and during the Covid-19 pandemic. This study uses Positive Accounting Theory and Contingency Theory as the basis for developing hypotheses with a sample of 168 obtained from 56 companies in Indonesia as one of the countries adopting International Financial Reporting Standards (IFRS) with a research period of 2018-2020. This study uses a regression test with research result showing that in the conditions of the Covid-19 pandemic with high uncertainty and limited information, the intensity of companies to capitalize on research and development expenditures is smaller than before the Covid-19 pandemic. This study provides an overview for companies in making decisions regarding the accounting treatment of expenditures for research and development, especially in conditions of uncertainty and limited information.